In silico investigations of albumin-GLP-1 receptor agonist complexes for diabetes drug delivery applications - Murphy, Gillian; Cheung, David; Fitzgerald, Michael; Pandit, Abhay (Computational and structural biotechnology journal, 2025)
This paper describes the specific conformational folding patterns and residues involved in stabilizing the Glucagon-like Peptide-1 Receptor Agonist (GLP-1 RA) peptide-albumin protein complex using molecular dynamic (MD) simulations and surface plasmon resonance (SPR). We quantified the binding energies, thermodynamics, conformational shifts and specific residue-residue interactions of the peptide-albumin complex. The study presents molecular-level findings of the relationship between these interactions and the formation of amide bonds in a PEGylated hydrogel drug delivery system. This research outlines the potential of harnessing MD simulations as a biomaterial characterisation tool, giving deeper insights beyond the established in vitro methods. Further research in this field could lead to advancements in the rational design and development of next generation controlled release formulations and long-acting GLP-1 RA therapeutics. [Display omitted]